Zur Notwendigkeit der Philosophie im Medizinstudium - Bohrer, Thomas; Schmidt, Michael; Königshausen, Johann-Heinrich (DMW - Deutsche Medizinische Wochenschrift, 2018)
Today, the study and practice of medicine are treated with a natural scientific approach. However, medical action has its foundations not only in the natural sciences and technology, but also in ethics, humanity and philosophy. The Wuerzburg Philosophicum teaches, apart from medical ethics, a systematic analysis of a theory of medicine in the context of other sciences, the theory of knowledge, anthropology and hermeneutics.
Keywords: Philosophie der Medizin; Würzburger Philosophikum